2018
DOI: 10.5194/cp-14-255-2018
|View full text |Cite
|
Sign up to set email alerts
|

Astronomical tunings of the Oligocene–Miocene transition from Pacific Ocean Site U1334 and implications for the carbon cycle

Abstract: Abstract. Astronomical tuning of sediment sequences requires both unambiguous cycle pattern recognition in climate proxy records and astronomical solutions, as well as independent information about the phase relationship between these two. Here we present two different astronomically tuned age models for the Oligocene-Miocene transition (OMT) from Integrated Ocean Drilling Program Site U1334 (equatorial Pacific Ocean) to assess the effect tuning has on astronomically calibrated ages and the geologic timescale.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 62 publications
2
38
0
Order By: Relevance
“…Their overall in-phase behaviour at 100-kyr time scales is characterized by an average lag of δ 13 C compared to δ 18 O of 1.9 kyr (0.12 rad) in Interval I, and 2.5 kyr (0.16 rad) in Interval II. This small but noticeable phase lag of δ 13 C has been observed before 10,49,50 and explained by thẽ 65 kyr residence time of carbon in the ocean 9,51 . The large size of the ocean carbon reservoir, in combination with a non-linear climate response to precessional forcing, causes the response time of the carbon cycle to eccentricity to be several thousand years slower than that of the climate-cryosphere system.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Their overall in-phase behaviour at 100-kyr time scales is characterized by an average lag of δ 13 C compared to δ 18 O of 1.9 kyr (0.12 rad) in Interval I, and 2.5 kyr (0.16 rad) in Interval II. This small but noticeable phase lag of δ 13 C has been observed before 10,49,50 and explained by thẽ 65 kyr residence time of carbon in the ocean 9,51 . The large size of the ocean carbon reservoir, in combination with a non-linear climate response to precessional forcing, causes the response time of the carbon cycle to eccentricity to be several thousand years slower than that of the climate-cryosphere system.…”
Section: Resultsmentioning
confidence: 61%
“…All Sites that constitute the δ 13 C megasplice are included here (references in Fig. 1 ) and are complemented by additional orbital-resolution benthic isotope data from Sites 926 82 , 982 83 , 1264/1265 15 , 49 , U1334 50 , 84 , U1337 17 and U1338 6 , 85 (data as time-series in Supplementary Fig. 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…A reassessment of the range charts from key biozonations has also been undertaken in order to determine whether certain bioevents were recognisable. A number of potential amendments to the low latitude biogeochronology of Wade et al (2011) have been suggested based upon the historical importance of certain bioevents, as well as updating the Miocene component to more recent magnetochronologies (Kochhann et al, 2016;Ogg et al, 2016;Drury et al, 2017;Beddow et al, 2018) and astronomically tuned records (Wilkens et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This tuning has been confirmed at the ~400 kyr eccentricity level using sedimentary records from the Atlantic Ocean, including ODP Leg 177 (Billups et al, 2004), ODP Leg 154 (Pälike et al, 2006a), ODP Leg 208 (Liebrand et al, 2016), and IODP Expedition 342 (Van Peer et al, 2017). A more recent eccentricity-tuned record from the equatorial Pacific (IODP Expedition 320/321; Beddow et al, 2018) confirmed the accuracy of the numerical ages across the Oligocene-Miocene transition to the ~100 kyr eccentricity level.…”
Section: Introductionmentioning
confidence: 55%
“…ice sheet, preceding the transient cooling and "re-glaciation" of Antarctica across the Oligocene-Miocene climatic transition (OMT; 23 million years ago; Billups et al, 2004;Pälike et al, 2006b;Liebrand et al, 2016;Beddow et al, 2018).…”
Section: Introductionmentioning
confidence: 99%